Liquid Ritualizing - Arfman, William R. (Journal of religion in Europe, 2014)
This article concerns itself with the challenges faced when “deliberately cultivating or inventing rites” (Grimes) in late modernity, a period which philosophers and sociologists describe as fluid, reflexive, risky, and post-traditional. Through analysis of the ritual field of collective commemoration, which in the last decades has emerged in the Netherlands, it is argued that such challenges are in fact overcome by an attitude of embracing the very aspects that characterize late modern times. This attitude is dubbed ‘liquid ritualizing,’ and it is contrasted to earlier forms of ‘rooted’ ritualizing in order to challenge certain fundamental claims regarding contemporary religiosity.